2020
DOI: 10.1186/s12863-020-00885-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, identification and expression profiling of genome-wide R-genes in melon and their putative roles in bacterial fruit blotch resistance

Abstract: Background: Bacterial fruit blotch (BFB), a disease caused by Acidovorax citrulli, results in significant economic losses in melon. The causal QTLs and genes for resistance to this disease have yet to be identified. Resistance (R)genes play vital roles in resistance to plant diseases. Since the complete genome sequence of melon is available and genome-wide identification of R-genes has been performed for this important crop, comprehensive expression profiling may lead to the identification of putative candidat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 84 publications
(98 reference statements)
0
11
0
Order By: Relevance
“…To further investigate and identify candidate genes contributing to ToLCNDV resistance or susceptibility, we analyzed the expression profile of 70 R-genes of melon previously characterized by Islam et al (2020) and other categories of genes related to the defense response in geminivirus infection, including gene silencing, pathogen-resistant proteins, and hormonal response.…”
Section: Resultsmentioning
confidence: 99%
“…To further investigate and identify candidate genes contributing to ToLCNDV resistance or susceptibility, we analyzed the expression profile of 70 R-genes of melon previously characterized by Islam et al (2020) and other categories of genes related to the defense response in geminivirus infection, including gene silencing, pathogen-resistant proteins, and hormonal response.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies revealed that these RGAs shared sequence similarities to the known R genes and were present abundantly in the genome of many plants ( McDowell and Simon, 2006 ). Later, RGAs were involved in the resistance mechanisms against different pathogens ( Zhang et al, 2013 ; Islam et al, 2020 ). The present investigation indicated an important role of RGAs in governing resistance in barley against B .…”
Section: Discussionmentioning
confidence: 99%
“…To further identify candidate genes related to WMV resistance, the expression profile of genes associated with plant defense responses against viruses were studied. We looked for R-genes previously characterized in melon [34], families of transcription factors (TFs) involved in stress responses, pathogen-resistant proteins, genes involved in gene silencing and hormonal signaling and susceptibility factors (Fig. 4).…”
Section: Expression Of Known Genes Related To Plant Defense Responsesmentioning
confidence: 99%